2022
DOI: 10.3126/njc.v6i2.48767
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopy findings in 1074 lung cancer patients in a tertiary care center in Nepal

Abstract: Background: Fiberoptic bronchoscopy is the most important diagnostic tool for lung cancer. Early tissue diagnosis and proper staging remains the key to the management of the lung cancer patient. Endobronchial forceps biopsy has high diagnostic yield from the visible lesions. The aim of the study was to evaluate diagnostic yield of endobronchial biopsy. Methods: A retrospective cross-sectional study was conducted at B.P. Koirala Memorial Cancer Hospital, Bharatpur, Nepal. Bronchoscopy reports of 1074 patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…22 the most common types of lung cancer were squamous cell carcinoma, followed by adenocarcinoma, SCLC, and NSCLC-not otherwise specified (NOS). 10,23,24 Women were more likely to have SCLC and adenocarcinoma, whereas men were more likely to have squamous cell carcinoma. Squamous cell carcinoma was more frequent in men and in patients older than 65 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 the most common types of lung cancer were squamous cell carcinoma, followed by adenocarcinoma, SCLC, and NSCLC-not otherwise specified (NOS). 10,23,24 Women were more likely to have SCLC and adenocarcinoma, whereas men were more likely to have squamous cell carcinoma. Squamous cell carcinoma was more frequent in men and in patients older than 65 years old.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in biopsy methods were statistically significant. 10,23,24 Recent advances in bronchoscopy have improved its diagnostic accuracy for lung cancer detection. A study conducted by Ishiwata, et al (2022) assessed the diagnostic accuracy of endobronchial ultrasonography with a guiding sheath (EBUS-GS) for detecting peripheral pulmonary lesions and found that EBUS-GS had a diagnostic yield of 86.4% and a sensitivity of 80.0%.…”
Section: Discussionmentioning
confidence: 99%